2018
DOI: 10.3892/ol.2018.7856
|View full text |Cite
|
Sign up to set email alerts
|

Colon cancers carrying BRAF V600E and β-catenin T41A activating mutations are resistant to numerous common anticancer drugs

Abstract: Abstract. Colorectal cancer is a common malignancy with a high prevalence and associated mortality rate. However, the preclinical tools currently used for drug development are insufficient. The aim of the present study was to establish and characterize a specific patient-derived colon cancer xenograft (PDCCX) mouse model for drug testing. Primary colon tumors were obtained from 10 patients by surgical resection, and tumor tissues were subsequently grafted into nude mice followed by consecutive passages. Primar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 38 publications
1
4
0
Order By: Relevance
“…Similarly, in the present study, the cytotoxicity of cetuximab was lower in CTNNB1 T41A, S45F and S33P mutant Caco-2 cells compared with the WT cells at all dosage levels. The results of Xu et al (35) strongly support the present results; however, the study could not reveal the individual effect of the CTNNB1 T41A mutation on cetuximab because the mice also had a BRAF mutation along with the CTNNB1 T41A mutation. On the other hand, the effects of S45F and S33P mutations on cetuximab resistance have not been studied before, to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 87%
See 3 more Smart Citations
“…Similarly, in the present study, the cytotoxicity of cetuximab was lower in CTNNB1 T41A, S45F and S33P mutant Caco-2 cells compared with the WT cells at all dosage levels. The results of Xu et al (35) strongly support the present results; however, the study could not reveal the individual effect of the CTNNB1 T41A mutation on cetuximab because the mice also had a BRAF mutation along with the CTNNB1 T41A mutation. On the other hand, the effects of S45F and S33P mutations on cetuximab resistance have not been studied before, to the best of our knowledge.…”
Section: Discussionsupporting
confidence: 87%
“…Cetuximab is a monoclonal antibody that specifically inhibits EGFR and has been used as a biological agent in CRC treatment (5) (14,(24)(25)(26)(27)(28)(29)(30)(31)(32)(33)(34)(35)(36)(37). Furthermore, the AKT1 E49K mutation has been observed in patients with bladder cancer (38), but not in patients with CRC.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In another experiment, we showed that a single DB pre-treatment (below IC50) could significantly reduce the tumor-initiating ability of IGF1-cultured DLD-1 colon CSC-like cells in vivo. Mechanistically, DB treatment was associated with the decreased expression of a key CSC marker, β-catenin, which has been shown to be aberrantly increased in malignant colon cancer cells and associated with the generation of drug-resistance [ 36 , 37 ]. DB-mediated suppression of β-catenin was also accompanied with an increased miR-214 level, which has a potential binding site at β-catenin’s 3′UTR.…”
Section: Discussionmentioning
confidence: 99%